Exploring students’ error in quadratic word-problem using Newman procedure / Teh Faradilla Abdul Rahman and Nurul Ardillah Abd Hamid Effendy - Abdul Rahman, Teh Faradilla; Abd Hamid Effendy, Nurul Ardillah (Universiti Teknologi MARA, Cawangan Melaka, 2019)
Mathematics worded problem solving is one of the difficult area for students. Some students were able to understand the question’s requirements but applied inefficient strategy to solve it which caused errors in their way of writing the solution. As it become more complex to adapt with real life and career in the future, it is important to detect students’ commonly made errors at the early stage. Teachers should also focus on improving students’ understanding before students move to the next level. In addition, issues of gender differences in mathematical errors must be look into depth to tackle their learning styles and thinking. Therefore, the aim of this study is to analyse students’ performance and to determine the types of errors that occur in students’ quadratic word-problem solving. This study also compares the different kinds of errors showed by male and female students in solving quadratic word problems. As many as 151 students were involved in answering six quadratic equations test. Their answers were then analysed to determine the performance, the type of error made and to identify the students individually. Next, 11 students who had been identified as the the students who made most error were interviewed. The items in the interview were adapted from Newman’s Error Analysis which includes five types of errors such as reading, comprehension, transformation, process skills and encoding. In this study, carelessness errors was added as a factor to indicate students who were passed the five errors but mistakenly came out with the wrong final answer. The findings showed that the students’ performance in solving quadratic word-problems is high, the errors commonly made by female students were comprehension, transformation and carelessness, while the male students dominating the highest frequency in transformation error.